A comparative study of reciprocity in international physician licensing. Issue 3 (26th August 2014) - Vivek Pande, Dr.; Pande, Vivek
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the international mobility of physicians by comparing the regulations governing the practice of foreign physicians in the USA and eight other countries. Design/methodology/approach – This is a comparative study of the regulations governing the practice of foreign physicians in eight countries: China, India, the Philippines, the UK, Germany, Denmark, Israel and Australia. Their requirements are then contrasted with the USA's requirements for foreign physician licensure to evaluate the extent of reciprocity among these countries. We conclude the paper by outlining some recommendations to increase the international mobility of physicians in the future. Findings – The results indicate that licensure for US physicians to practice in the nations above ranges from impossible (India), to difficult (China), to moderately difficult (the UK, Germany and Denmark), to easy and completely reciprocal (Australia, Israel and the Philippines). Originality/value – The results and recommendations in this study are a valuable starting point for further research and policy changes that will ensure a more reciprocal relationship between the USA and other countries, in terms of opportunities for international medical practice.